Premature valve closure in patients with a mitral Starr-Edwards prosthesis and aortic incompetence - Agnew, T. M. (1970)
A mitral Starr-Edwards ball valve has, in three patients with concomitant aortic incompetence, permitted recognition of intermittent premature valve closure by auscultation and this has been documented by phonocardiograms. In two instances the observations were confirmed during cardiac catheterization. The features of premature Starr valve closure are described and the mechanism is discussed.